Design of a Rice Weighing Tool with Sound Output Using Arduino Uno - Alfianda; Hamdi, Nurul (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
Technological developments are currently growing increasingly widespread. This causes conventional equipment to be replaced with more sophisticated and fully automated equipment. This research aims to implement the design of a rice-weighing device with sound output using Arduino Uno. Meanwhile, the benefit you get is knowing the weight of the rice to be weighed and being able to simplify the process of selling rice for traders who sell rice. The research method for this tool uses input, output, and control processes. The load cell functions as an input that calculates the weight, the Arduino functions as a controller for all circuits, and the player and LCD are outputs that display prices. This rice weighing tool is designed in the form of a digital scale which aims to simplify the process of reading the weight of rice on the scale. The test results of this digital scale are that when the weight of rice is above 500 grams, this tool produces a sound output and displays the total price according to the importance of the rice.